SANKSI PAJAK ATAS BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN KURANG BAYAR YANG TIDAK SESUAI DENGAN NILAI PEROLEHAN OBJEK PAJAK YANG SEHARUSNYA DI KOTA MEDAN - ANDREAS RAJAGUKGUK (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Prof. Dr. Budiman Ginting, SH, MHum2.  Dr. Bastari, MM3.  Dr. Utary Maharany Barus, SH, MHum AbstractIn practice, the implementation of transaction value as the basiccalculation of BPHTB (Duty on Land and Building Right Acquisition) frequentlycauses problems because it is not uncommon that transaction value proposed bytaxpayers is not in accordance with what has been expected by tax officers. Theresearch problems are how about the authority of tax authorities in verifyingBPHTB collecting in Medan, how about the efforts to determine underpaidBPHTB which is not in accordance with the Due Acquisition Value of Tax Objectin Medan, and how about the administrative sanction of taxation that can beimposed upon underpaid BPHTB by taxpayers in Medan.Keywords: Tax Sanction for Underpaid BPHTB